Non-Collocated Position Control of Steel Strip With Electromagnetic Rejection of Unknown Multi-Harmonic Disturbances. Issue 15 (2019) - Saxinger, M.; Marko, L.; Steinboeck, A.; Kugi, A.
Abstract: Many industrial processes are affected by periodic disturbances. For instance, vibration of steel strips in hot-dip galvanizing lines entail an inhomogeneous zinc coating of the final product. Excitation by periodic disturbances is also frequently encountered in other control systems. Thus, a number of customized methods for rejection control of unwanted oscillations have been developed in the literature. In this paper, a method for eliminating a multi-harmonic periodic disturbance at an arbitrary user-defined position of a steel strip is proposed. The control task is particularly complicated because the disturbance input, a (single) displacement sensor, a (single) electromagnetic actuator, and the system output to be controlled are located at different positions along the strip. In addition, the electromagnetic actuator used as control input features neither a force sensor nor a distance sensor for measuring the air gap between the strip and the magnetic core. Hence, the actuator operates in a pure feedforward mode. The developed control method is validated by means of an experimental test rig that mimics a scenario from an industrial hot-dip galvanizing line.